On The Limits Of The Lorawan Technology: Evaluation Of Spreading Factors’ Performance - Možný, Radek (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2020)
Over the course of the recent decade, the Low-Power Wide-Area (LPWA) technologies took their momentum and started to enable the reliable data transmissions in the Internet of Things (IoT) and Industry 4.0. In this paper, the LoRaWAN communication technology i.e., the licenseexempt LPWA technology is described. The focus is given to the practical evaluation of different configurations of the Spreading Factor (SF) based on the signal level. The obtained results from the laboratory measurements confirm the suitability of lower SFs in case of decreased signal levels i.e. conditions close to the “deep indoor scenarios”.
Keywords: LoRaWAN; Spreading Factors; LPWA; Internet of Things; Industry 4.0